2018
DOI: 10.3390/min8020032
|View full text |Cite
|
Sign up to set email alerts
|

Copper Bioleaching in China: Review and Prospect

Abstract: The commercial application of copper bioleaching, an environmentally-friendly approach for low-grade and secondary mineral resources recycling, has increased worldwide since the 2000s. As the world's second-largest economic entity and the largest developing country, China has the largest demand for metal resources, significantly advancing the theory and industrial technology of copper bioleaching. This paper reviews the exploration and application of copper bioleaching in China. Two typical bioleaching applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 233 publications
(231 reference statements)
1
22
0
1
Order By: Relevance
“…5a). When microorganisms colonized on the mineral surface, chalcopyrite was dissolved through a direct mechanism, as shown in eqn (1), which was in line with increasing trend of pH during the initial bioleaching process (Fig. 2c).…”
Section: Mechanism Of Different Exogenous Consortia On Chalcopyrite Bsupporting
confidence: 67%
“…5a). When microorganisms colonized on the mineral surface, chalcopyrite was dissolved through a direct mechanism, as shown in eqn (1), which was in line with increasing trend of pH during the initial bioleaching process (Fig. 2c).…”
Section: Mechanism Of Different Exogenous Consortia On Chalcopyrite Bsupporting
confidence: 67%
“…These concentrations are sometimes detected in surface water, sediments, and surface soils around unexploited deposits [7,8]. Moreover, mining activities can trigger the leaching of large quantities of HMs into the environment [9], particularly during opencast mining and smelting activities as they exert substantial environmental impact on soils and water streams [10]. The European industrial sector reported that mining and metal processing industries contribute to 48% of the total release of HMs contaminants [11].…”
Section: Introductionmentioning
confidence: 99%
“…As an environmentally friendly, lower cost, and efficient recycling method of valuable metal resources, the solution mining method has been widely utilized in the recycling of lower grade minerals, mine tailings, and wastes [1][2][3]. It is commonly recognized that valuable metal ions continuously transfer between the reaction interface and the leaching solution, eventually obtaining pregnant leaching solution (PLS) and metal products [4].…”
Section: Introductionmentioning
confidence: 99%